THE MACHINE METHOD FOR PROCESSING CHICKEN FEATHERS BY SPLITTING THEM INTO FIBERS AND RACHIS - Paşayev, Nazim; Tekoğlu, Onur; Kocatepe, Süreyya; Erol, Müslüm; Maraş, Nesli (Chamber of Textile Engineers, 2021)
Chicken feathers are obtained as a by-product in the production of poultry meat. Due to its stiffness, fragility and inelasticity, chicken feathers are not considered a valuable material and are mostly industrial waste, the volume of which is increasing. Therefore, chicken meat producers are trying to get rid of them in every possible way. In recent years, instead of getting rid of chicken feathers, research has been carried out towards using their wonderful properties from nature. Among these studies, a special place is occupied by the production of fibers from chicken feathers, which could be used in the textile industry. The presented work concerns the development of a mechanized method for the production of fiber from chicken feathers on an industrial scale. The proposed method is based on the separation of the fibrous part of the feather from the stem of the feather by mechanical cutting using an aerodynamic disperser. With this method, protein fibers with many valuable properties have been obtained, the weight of which is half that of chicken feathers. In addition to these fibers, called chicken feather fibers, a feather stalk is obtained as a by-product, which, due to its lightness and strength, is a suitable raw material for the production of composites. In this work, the properties of the products obtained by the above-mentioned method were studied, and it was determined that the materials obtained as a result of processing the produced chicken feathers are raw materials suitable for industrial use. The production parameters of the machine used to separate the fibers from the stem were also investigated and it was observed that the operating parameters of the machine did not adversely affect the natural properties of the fibers produced. © 2021,Tekstil ve Muhendis.All Rights Reserved
Keywords: Chicken feather; Chicken feather fibers; Chicken feather rachis; Feather processing